2004
DOI: 10.1213/01.ane.0000134796.83697.cd
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Central Anticholinergic Syndrome in a 6-Week-Old Infant

Abstract: A 6-wk-old male infant became unresponsive after an uneventful general anesthetic for hernia repair. His symptoms were consistent with central anticholinergic syndrome. He appeared to awaken after treatment with IV physostigmine in a dose of 0.04 mg/kg. Because of the recurrence of sedation, a second physostigmine infusion was administered, which again led to transient arousal. Finally, the patient awoke spontaneously after 24 h and recovered uneventfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…19 The true incidence of CAS is unknown. The incidence of CAS has been reported to range from 1% to 40%.…”
Section: Incidence Of Casmentioning
confidence: 99%
“…19 The true incidence of CAS is unknown. The incidence of CAS has been reported to range from 1% to 40%.…”
Section: Incidence Of Casmentioning
confidence: 99%
“…Central anticholinergic syndrome (CAS) typically occurs in adults after large (or repeated small) doses of atropine . However, it has been suspected in a child as young as 6 weeks old . The prevalence of CAS has been previously reported to be 9.4% after general anesthesia and 3.3% after regional anesthesia with sedation .…”
Section: Introductionmentioning
confidence: 99%
“…However, in a more recent prospective study, Link et al found an incidence of only 1.9% in patients undergoing elective surgery under general anesthesia . The wide range of reported incidences may be the result of changing anesthesia practices (e.g., decrease in the use of atropine for premedication) and the challenge of diagnosing CAS …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequencies of CAS between 1-11.2% have been reported after general anesthesia. CAS is well-defined in elderly adults but it has only been reported rarely in children (4)(5)(6)(7)(8)(9), and only a single case in infants (5).…”
Section: Introductionmentioning
confidence: 99%